1992
DOI: 10.1002/j.1460-2075.1992.tb05022.x
|View full text |Cite
|
Sign up to set email alerts
|

A missense mutation in the vasopressin-neurophysin precursor gene cosegregates with human autosomal dominant neurohypophyseal diabetes insipidus.

Abstract: Familial neurohypophyseal diabetes insipidus in humans is a rare disease transmitted as an autosomal dominant trait. Affected individuals have very low or undetectable levels of circulating vasopressin and suffer from polydipsia and polyuria. An obvious candidate gene for the disease is the vasopressin‐neurophysin (AVP‐NP) precursor gene on human chromosome 20. The 2 kb gene with three exons encodes a composite precursor protein consisting of the neuropeptide vasopressin and two associated proteins, neurophysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(31 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…No mutations relative to the previously published sequences (Sausville et al, 1985;Bahnsen et al, 1992) were identified. Restriction sites, in the primers or plasmid, were utilized for sub-cloning into chloramphenicol acetyl transferase (CAT) reporter constructs.…”
Section: Construction Of Reporter Plasmidsmentioning
confidence: 73%
See 1 more Smart Citation
“…No mutations relative to the previously published sequences (Sausville et al, 1985;Bahnsen et al, 1992) were identified. Restriction sites, in the primers or plasmid, were utilized for sub-cloning into chloramphenicol acetyl transferase (CAT) reporter constructs.…”
Section: Construction Of Reporter Plasmidsmentioning
confidence: 73%
“…Although 1.2 kb of the 5′ promoter region for human AVP has been cloned and sequenced (Bahnsen et al, 1992), this has been only partially characterized and no SCLC-specific elements have been identified. We amplified this region by PCR, as described in detail in Methods and shown diagrammatically in Figure 1B.…”
Section: Cloning Of the Avp Promoter And Enhancer Regionsmentioning
confidence: 99%
“…The disorder is transmitted in an autosomal dominant manner, and typically presents in early childhood, apparently reflecting the progressive loss of AVP secretion in response to increased serum osmolality (7,8). Numerous mutations within the AVP gene have been identified recently in patients with FNDI (6,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The mutations are distributed throughout the precursor protein, and include missense mutations within the signal sequence (10,12,13,17), the AVP peptide (17a), and the NP domain (6,9,11,(14)(15)(16)18).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we present the clinical features of two patients with neurohypophyseal DI, not related to the earlier described Dutch families with this disease (9,10), caused by a novel mutation in the AVP-NPII gene.…”
Section: Introductionmentioning
confidence: 98%